The Effectiveness of Corneal Epithelial Debridement Performed with an Alcohol-Impregnated Sponge - Altinbay, Deniz; Taskin, Ibrahim (Klinische Monatsblätter für Augenheilkunde, 2021)
Objective To evaluate the clinical outcomes of patients who underwent corneal surgery with debridement of epithelium by localised application of an alcohol-impregnated sponge instead of the usual alcohol reservoir method.Design This study retrospectively included 52 eyes of 27 patients who underwent LASEK (laser-assisted subepithelial keratectomy) and CXL (cross-linking) surgery after application of this alcohol-assisted debridement method between January 2019 and April 2019.Participants Twenty-four patients who underwent LASEK and three patients who underwent CXL surgery were included in this study, which comprised a total of 52 eye operations.Methods Epithelial debridement was performed after placing a 20% ethanol-impregnated sponge on the cornea for 20 seconds.Results The mean pachymetry value was 509.40 ± 30.37 µm, the mean preoperative spherical equivalent was − 2.14 ± 1.02 dioptres, and the highest myopia and astigmatism values were − 4.25 dioptres and − 2.75 dioptres, respectively. It was seen that the corneal epithelium was completely and easily debrided in a size identical to that of the applied sponge.Conclusions Complete debridement of the corneal epithelium can be performed quickly, safely, and easily with this specially prepared sponge.
Keywords: alcohol-impregnated sponge; cornea; debridement; laser-assisted subepithelial keratectomy; pachymetry